(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article compares the viability and effectiveness of local medical leeches collected from the Fergana Valley and imported medical leeches from Turkey and Azerbaijan. Local medical leeches have been found to be superior to imported leeches in terms of both viability and reproductive efficiency.